Perancangan dan Pengembangan Sistem Informasi Permintaan ATK untuk PT. Wilmar Bioenergi Indonesia - Yopy Renaldi; Ahmad Jurnaidi Wahidin; Yusuf Unggul Budiman; Risa Prayudhi (LPPM STT Terpadu Nurul Fikri, 2026)
The research problem addressed in this study is the manual process of requesting and recording office stationery (ATK) at PT. Wilmar Bioenergi Indonesia, which leads to process delays, data inaccuracies, and difficulties in reporting. This study aims to design and implement a web-based ATK request information system to support more effective and efficient administrative management. The prototype method was employed, with data collected through observation, interviews, and literature review. The system was developed using PHP, MySQL, and the Bootstrap framework, and evaluated using Black Box Testing. The results indicate that the system supports integrated ATK request submission, approval, and reporting processes, with all main features functioning as expected. The contribution of this study lies in providing a web-based ATK request information system model that enhances internal administrative effectiveness and can serve as a reference for developing ATK request management systems in similar organizations.